The Effect of Secang Wood (Caesalpinia sappan L.) Extract to Number of Iodine and Peroxide of Groundnut Cake - Rusdi, UD; Widowati, W; Sudiarto, Sudiarto (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
This research aimed to analyze the ability of secang wood extract (EKS) to retain the degradation rate of iodine number and to decelerate the peroxide number the represents the occurrences of damage at groundnut cake (BKT) during its storage. Research conducted by experimental method using completely randomized design with 7x5 factoria. Number of iodine and number of peroxide of groundnut cake were assessed. Result showed that with the application of secang wood extract, a 60 days stored groundnut cake had a higher number of iodine and lower number of peroxide compared to both, control, and BKT treated with hydroxytoluene butylated (BHT) 0.1% and benzoate natrium (NB) 0.1%. (Animal Production 7(3): 150-155 (2005) Key Words : Groundnut cake, Iodine, Peroxide